(untitled) (International Journal of Biology and Chemistry, 2026)
Drought is one of the most critical environmental constraints limiting wheat productivity worldwide, especially under organic and low-input agricultural systems where synthetic fertilizers are restricted. Microbial inoculants, particularly plant growth-promoting rhizobacteria (PGPR), offer a sustainable strategy for enhancing plant tolerance to water deficit by improving physiological performance and nutrient acquisition. In this study, germinated seeds of the wheat cultivar ‘Rakhshan’ were inoculated with eight PGPR strains – Azotobacter chroococcum (Azto478), A. salinestris (Azto474), Azospirillum lipoferum (A443), Pseudomonas sp. (P196 and P241), Pseudomonas fluorescens (P187), Pseudomonas putida (P186), and Bacillus subtilis (B271). The experiment was conducted under greenhouse conditions using a completely randomized factorial design. Drought stress was applied at three moisture levels corresponding to 100%, 60%, and 40% of field capacity (FC), and soil moisture was maintained throughout the 100-day growth period. Measured traits included grain, shoot, and root dry weights; plant height; spike length; grain nitrogen, phosphorus, and potassium concentrations. As expected, increasing drought severity markedly reduced all growth and nutrient parameters. However, PGPR inoculation substantially mitigated these declines, demonstrating the capacity of specific bacterial strains to counteract drought-induced physiological limitations. Among the tested inoculants, Pseudomonas fluorescens P187 consistently exhibited the strongest positive effects. Under moderate drought, P187 increased grain dry weight by approximately 95%, and under severe drought it enhanced shoot and root dry weights by approximately 75% compared with the uninoculated control. P187 also improved macronutrient accumulation, outperforming all other strains across nitrogen, phosphorus, and potassium contents. Pseudomonas sp. P196 ranked second, showing notable but comparatively lower improvements. Overall, the findings identify P187 and to a lesser extent P196 as highly promising PGPR candidates for developing microbial biofertilizers aimed at enhancing drought resilience and nutrient use efficiency in wheat. These strains warrant further evaluation under field conditions and in multi-strain or consortium-based formulations to maximize their agronomic potential. Key words: biofertilizers, drought, inoculation, stress mitigation, water deficit, wheat.